Anti‐N‐Methyl‐D‐aspartate receptor encephalitis masquerading as fever of unknown origin. Issue 4 (4th March 2021) - Heng, Katrina Yi Ching; Lee, Jan Hau; Thomas, Terrence
Abstract: Fever of unknown origin (FUO) is a diagnostic challenge. Anti‐N‐methyl‐D‐aspartate receptor encephalitis should be considered in children with FUO and new‐onset neurological symptoms without significant encephalopathy. Abstract : Fever of unknown origin (FUO) is a diagnostic challenge. Anti‐N‐methyl‐D‐aspartate receptor encephalitis should be considered in children with FUO and new‐onset neurological symptoms without significant encephalopathy.